Corporate R&D and firm efficiency: Evidence from Europe's top R&D investors - Subal C. Kumbhakar; Raquel Ortega-Argilés; Lesley Potters; Marco Vivarelli; Peter Voigt (European Commission, Joint Research Centre (JRC), 2010)
The main objective of this study is to investigate the impact of corporate R&D activities on firm performance, measured by labour productivity. To this end, the stochastic frontier technique is used on a unique unbalanced longitudinal dataset on top European R&D investors over the period 2000–2005. The study quantifies technical inefficiency of individual firms. From a policy perspective, the results of this study suggest that – if the aim is to leverage firms' productivity – emphasis should be put on supporting corporate R&D in high-tech sectors and, to some ex-tent, in medium-tech sectors. On the other hand, corporate R&D in the low-tech sector is found to have a minor effect in explaining productivity. Instead, encouraging investment in fixed assets appears important for the productivity of low-tech industries. Hence, the allocation of support for corporate R&D seems to be as important as its overall increase and an `erga omnes' approach across all sectors appears inappropriate. However, with regard to technical efficiency, R&D intensity is found to be a pivotal factor in explaining firm efficiency. This is true for all industries.
Keywords: L2; O3; 330; Corporate R&D; productivity; technical efficiency; stochastic frontier analysis